The Influence of Employee Engagement and Work Motivation on Employee Loyalty: A Systematic Literature Review Using the PRISMA Method (Case Study on Employees of PT. XXX Area HQ) - Siska Yulia; Eko Budi Soetjipto; Madziatul Churiyah (JURNAL ECONOMINA, 2026)
This study aims to analyze the development of research on employee engagement , work motivation, and employee loyalty through approach Systematic Literature Review (SLR) and bibliometric analysis. The research uses method PRISM ( Preferred Reporting Items for Systematic Reviews and Meta- Analyses ) for the systematic identification, screening, evaluation, and selection of articles. Research data was obtained from the Scopus database with a publication range of 2020-2026 using the keywords employee engagement , work motivation , and employee loyalty . Bibliometric analysis was conducted using the [Unclear text] tool. soft VOSviewer For map connection between keywords, research trends, country collaborations, and developments in research themes. The results show a significant increase in publications related to employee loyalty, employee engagement, and work motivation in the 2023-2025 period. Keyword co-occurrence analysis yielded three main clusters: work motivation , employee management , and employee loyalty . The research findings indicate that work motivation, human resource management practices, and employee engagement have a significant influence on the formation of employee loyalty. Geographically, the Asia-Pacific region dominates the development of research, particularly Malaysia, Australia, and Macau. This study confirms that employee loyalty is a strategic issue in modern organizations, so companies need to implement HR management that is oriented towards employee engagement, motivation, and well-being.